Association of a promotional campaign for local dining facilities with the occurrence of COVID-19 in Asahikawa City, Japan, in November 2021 - Sakiko Tabata Kuribayashi; Takuya Yamagishi; Naoki Suzuki; Go Asari; Rieko Abo; Harumi Yamamoto; Kazunori Yasutomi; Tsukasa Ohara; Yasuko Tachibana; Tomoe Shimada; Tomimasa Sunagawa (Elsevier, 2023)
Objectives: As social restrictions of COVID-19 are being eased worldwide, preventing SARS-CoV-2 transmission among staff members and customers in dining facilities is essential to continuously running business because restaurants and bars are high-risk locations for COVID-19 outbreaks. In 2021, COVID-19 outbreaks occurred at restaurants or bars in Asahikawa city, Japan two weeks after the launch of a promotional campaign for local dining facilities. We investigated this event to assess the association between the promotional campaign and the occurrence of SARS-CoV-2 infection. Study design: Cohort study. Methods: We assessed the association between the occurrence of COVID-19 cases in the restaurants and bars and their participation in the campaign by calculating risk ratio and 95% confidence interval. Results: Cases were identified among workers or customers in 4.0% (4/101) of the participating restaurants or bars and in 1.2% (39/3257) of the non-participating restaurants or bars. The risk ratio was 3.3 (95% confidence interval 1.2-9.0). Conclusion: The association between the occurrence of SARS-CoV-2 infection in the restaurants or bars and participation in the campaign is undeniable. Promotional campaigns to vitalize dining facilities should be accompanied by enhanced infection prevention measures, especially ventilation.